Retracted: Prevalence and the factors influencing soil transmitted helminths among school age children of 5 to 14 years in a rural area of Coimbatore district - Rajan, Xavier C.; Manivasagan, Sivamani; Boppe, Appalaraju (International Journal Of Community Medicine And Public Health, 2019)
The article "Prevalence and the factors influencing soil transmitted helminths among school age children of 5 to 14 years in a rural area of Coimbatore district" is retracted by the Editor-in-Chief, due to violation of the policies and practices of International Journal of Community Medicine and Public Health. The article is retracted on request of corresponding author and co-authors due to some errors in data which happened by the authors unintentionally.